Translating iGlarLixi Evidence for the Management of Frequent Clinical Scenarios in Type 2 Diabetes - Skolnik, Neil (Adv Ther, 2021)
Treatment of type 2 diabetes (T2D) requires progressive therapy intensification to reach and maintain individualized glycemic targets. iGlarLixi, a fixed-ratio combination of insulin glargine 100 U/mL (iGlar) and lixisenatide (Lixi), has been shown to provide robust HbA(1c) reductions allowing more people to reach HbA(1c) targets compared with separate administration of iGlar or Lixi. The purpose of this review is to help clinicians understand treatment intensification using iGlarLixi by presenting typical clinical scenarios supported by research evidence. These cases will focus on individuals with T2D inadequately controlled by oral antihyperglycemic drugs, basal insulin, or glucagon-like peptide-1 receptor agonists (GLP-1 RAs), and take into consideration T2D duration, body mass index, incidence of adverse events, and regimen simplicity. Clinical evidence on the efficacy, effectiveness, and safety of iGlarLixi from randomized controlled trials and real-world studies will be discussed in the context of these cases.